Consensus on the therapeutic management of atopic dermatitis ‒ Brazilian Society of Dermatology: an update on phototherapy and systemic therapy using e-Delphi technique - Raquel Leao Orfali; Daniel Lorenzini; Aline Bressan; Anber Ancel Tanaka; Ana Maria Mósca de Cerqueira; André da Silva Hirayama; Andréa Machado Coelho Ramos; Carolina Contin Proença; Claudia Marcia de Resende Silva; Cristina Marta Maria Laczynski; Francisca Regina Carneiro; Gleison Duarte; et al. (Sociedade Brasileira de Dermatologia, 2023)
Abstract This publication is an update of the "Consensus on the therapeutic management of atopic dermatitis - Brazilian Society of Dermatology" published in 2019, considering the novel, targeted-oriented systemic therapies for atopic dermatitis. The initial recommendations of the current consensus for systemic treatment of patients with atopic dermatitis were based on a recent review of scientific published data and a consensus was reached after voting. The Brazilian Society of Dermatology invited 31 experts from all regions of Brazil and 2 international experts on atopic dermatitis who fully contributed to the process. The methods included an e-Delphi study to avoid bias, a literature search and a final consensus meeting. The authors added novel approved drugs in Brazil and the indication for phototherapy and systemic therapy for AD. The therapeutical response to systemic treatment is hereby reported in a suitable form for clinical practice and is also part of this updated manuscript.